Book Review: The Principles of Good Corporate Governance and Law Enforcement - Imam Mustofa (Millah: Journal of Religious Studies, 2007)
Title          : Penerapan Good Corporate Governance                   (Mengesampingkan Hak-hak Istimewa Demi                    Kelangsungan Usaha)Writer        : Indra Surya & Ivan Yustiavandana        Publication  : 2006                Publisher    : KencanaPages        : xii + 243 pages